Work in the Changing Canadian Society - Smucker, Joseph (Labour / Le Travail, 1987)
This article reviews the book, "Work in the Changing Canadian Society," by Mervin Y. T. & Thomas G. Regan.
Keywords: Nonfiction; REGAN; Thomas G.; REVIEWS; WORK in the Changing Canadian Society (Book); Work environment; YAOTSU Chen; Mervin; books

Labour deployment in plants in Canada and Sweden - Smucker, Joseph; Van Den Berg, Axel; Smith, Michael R.; Masi, Anthony C. (Relations industrielles / Industrial Relations, 1998)
In the debates about the relationship between labor flexibility and employment security, the actual strategies managers employ under different policy regimes tends to be overlooked. The nature of deployment strategies that managers employ for their retained labor force in production plants in Canada and Sweden in 3 industrial sectors - steel, pulp and paper and telecommunications - is examined. While Canadian managers have greater access to external markets and make greater use of layoff-recall strategies and overtime than their Swedish counterparts, deployment strategies within plants tend to require more formal negotiations, especially within unionized plants. Swedish managers can carry out changes in labor deployment in a more informal manner, particularly with respect to job responsibilities and new skills training. Swedish managers face more difficulties than their Canadian counterparts in altering quantities of labor.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Cross cultural studies; Labor Unions; Labor relations; Manyindustries; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Strategic management; Workforce planning